Higher Education Curriculum Orientation and Performance of Universities in Kenya: Industry Linkage Strategies - Ngala, Orucho M. (Machakos University, 2019)
Quality education and training can only be achieved by orienting the academic curriculum in such a way that its content reflects industry demands. It must also be continuously reviewed after every cycle to capture the emerging issues in the dynamic economic environment. This study sought to contribute to knowledge by assessing the extent to which linking university curricula to the needs of the industry would influence performance of universities in Kenya. Resource based view was used as the main theory anchoring the study. Cross-Sectional survey was adopted as the research design. The population of the study consists of sixty five (65) public and private universities incorporated in Kenya. Out of this, a sample of forty seven (47) universities which had undergone at least one (1) graduation cycle was taken. Primary and secondary data was collected using semi structured questionnaires and review of existing university documents and regulatory bodies websites respectively. Correlation and regression analyses were used to test hypotheses. ANOVA was used to determine the differences between group means. Balanced score card was appropriately used to represent financial and non-financial aspects that constitute performance indicators. It was established that positive and significant correlations existed between curriculum orientation and university performance. The findings offer insight to university authorities and policy makers by reinforcing the role of collaborative strategies when developing and reviewing academic curricula. University authorities need to enhance collaboration with the industry in order to substantially exploit the synergies resulting from enhanced symbiotic correlations between university and the industry. The main limitation of this study is that primary data was collected from only one respondent per university but common methods bias was mitigated through the use of additional secondary data to validate primary data. Thus, the limitation did not affect the credence of the results as presented and discussed
Keywords: Curriculum Orientation; Linkage Strategy; Industry; Performance; University